2018
DOI: 10.3390/catal8110506
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Co-Pyrolysis of Kraft Lignin with Refuse-Derived Fuels Using Ni-Loaded ZSM-5 Type Catalysts

Abstract: The catalytic co-pyrolysis (CCP) of Kraft lignin (KL) with refuse-derived fuels (RDF) over HZSM-5, Ni/HZSM-5, and NiDHZSM-5 (Ni/desilicated HZSM-5) was carried out using pyrolyzer-gas chromatography/mass spectrometry (Py-GC/MS) to determine the effects of the nickel loading, desilication of HZSM-5, and co-pyrolysis of KL with RDF. The catalysts were characterized by Brunauer–Emmett–Teller surface area, X-ray diffraction, and NH3-temperature programed desorption. The nickel-impregnated catalyst improved the cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Synergistic effect was observed due to the balance between hydrogen and oxygen in the feedstock. Recently, Park et al investigated the catalytic co-pyrolysis of Kraft lignin with refuse-derived fuels [17]. As shown in Figure 4, the yields of aromatic hydrocarbons was much higher than the theoretical value for all catalysts, which could be attributed to the synergistic effect of hydrogen rich feedstock co-feeding.…”
Section: Pyrolysis Of Lignin To Oil Over Ni-based Catalystsmentioning
confidence: 91%
See 1 more Smart Citation
“…Synergistic effect was observed due to the balance between hydrogen and oxygen in the feedstock. Recently, Park et al investigated the catalytic co-pyrolysis of Kraft lignin with refuse-derived fuels [17]. As shown in Figure 4, the yields of aromatic hydrocarbons was much higher than the theoretical value for all catalysts, which could be attributed to the synergistic effect of hydrogen rich feedstock co-feeding.…”
Section: Pyrolysis Of Lignin To Oil Over Ni-based Catalystsmentioning
confidence: 91%
“…Comparison of experimental and theoretical value of (a) aromatic hydrocarbons and (b) phenolics from the catalytic co-pyrolysis of Kraft lignin and refuse-derived fuels over different catalysts[17].…”
mentioning
confidence: 99%
“…For example, it has been reported that Fe-ZSM-5 produced higher levels of deoxygenation and higher aromatisation efficiency associated with enhanced hydrogen transfer compared with unmodified ZSM-5 catalyst [6]. In addition, Lee et al [52] reported that co-pyrolysis-catalysis with Co-ZSM-5, Ni-ZSM-5, Zn-ZSM-5 and Fe-ZSM-5 catalysts produced lower catalyst coke formation compared with unmodified ZSM-5. Ni-ZSM-5 catalyst was also reported to increase the formation of aromatic hydrocarbons and alky phenols with reduced formation of alkoxy phenols due to induced increased hydrogen transfer from the plastic due to the nickel metal [52].…”
Section: Oil Composition From the Co-pyrolysis-catalysis Of Biomass:polystyrenementioning
confidence: 99%
“…In addition, Lee et al [52] reported that co-pyrolysis-catalysis with Co-ZSM-5, Ni-ZSM-5, Zn-ZSM-5 and Fe-ZSM-5 catalysts produced lower catalyst coke formation compared with unmodified ZSM-5. Ni-ZSM-5 catalyst was also reported to increase the formation of aromatic hydrocarbons and alky phenols with reduced formation of alkoxy phenols due to induced increased hydrogen transfer from the plastic due to the nickel metal [52]. Figures 5 and 6 also show enhanced yields of single-ring aromatic hydrocarbons with Ni-ZSM-5 and Fe-ZSM-5 catalysts compared to the other metal-modified and unmodified ZSM-5 catalysts.…”
Section: Oil Composition From the Co-pyrolysis-catalysis Of Biomass:polystyrenementioning
confidence: 99%
“…However, the shortcomings of zeolite catalysts are evident; for example, the narrow pore structure of the zeolite does not allow the passage of larger compounds leading to polymerization reactions at the surface to form coke. Therefore, the density and activity of the acidic part of the zeolite can be adjusted by introducing metallic substances to reduce catalyst deactivation and improve the selectivity of the bio-aromatics. For example, Vichaphund et al researched the production of bio-aromatics from Jatropha residues on Mo/HZSM-5 catalyst at 500 °C. Compared with the unmodified HZSM-5 catalyst, the Mo-modified HZSM-5 catalyst has a higher BTX yield (about 78.9%).…”
Section: Mechanism Of Bio-aromatics Preparationmentioning
confidence: 99%